2012
DOI: 10.1002/clc.22028
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Glycosylated Hemoglobin and Myocardial Perfusion Imaging

Abstract: Background:The relationship between long-term glucose control (measured by glycosylated hemoglobin [HgbA1C]) and myocardial perfusion imaging (MPI) abnormalities in symptomatic diabetic patients has not been studied. Hypothesis: We hypothesized that diabetic patients with poorly controlled HgbA1C would have more abnormal MPI compared to both patients without diabetes and diabetic patients with tighter glycemic control. Methods: This was a retrospective evaluation of 1037 consecutive patients referred for MPI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…25 SBP and DBP were significantly higher (p<0.05) in T2DM compared to controls. Our results are also supported by similar studies in India 26 and in USA, 27 which showed significantly higher (p<0.05) SBP and DBP in T2DM patients compared to normal controls. The hypertension is also suggestive of cardiovascular complications in DM patients.…”
Section: Discussionsupporting
confidence: 90%
“…25 SBP and DBP were significantly higher (p<0.05) in T2DM compared to controls. Our results are also supported by similar studies in India 26 and in USA, 27 which showed significantly higher (p<0.05) SBP and DBP in T2DM patients compared to normal controls. The hypertension is also suggestive of cardiovascular complications in DM patients.…”
Section: Discussionsupporting
confidence: 90%
“…The UK Prospective Diabetes Study showed that better glycemic control was associated with a reduction in both CAD prevalence and mortality after a mean of 10 years of follow-up.¹ 7 Although this is a cross-sectional and retrospective study, poorer glycemic control amongst the subjects with diabetes was associated with more extensive ischemia and infarction on MPI scanning. These findings are in accord with those reported by DeLuca et al and Nicole et al 11 , 12 In a retrospective chart review, DeLuca et al demonstrated that the prevalence of silent myocardial ischemia detected by MPI in diabetic patients who had no known CAD was higher in those with HbA 1c ≥7.6% than in those with HbA 1c <7.6% (50% versus 28%, P <0.005). Nicole et al demonstrated that the risk and prevalence of abnormal MPI (ischemia, infarction, or mixed defect) in patients with symptoms of CAD was greater in diabetic patients than in those without diabetes (41% versus 28%, P <0.001).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the prevalence of silent myocardial ischemia was greater in patients with poorly controlled diabetes (HbA 1c >7.6%) as compared with those with optimal glycemic control (HbA 1c <7.6%).¹¹ Another study found that the risk for abnormal MPI and the prevalence of myocardial ischemia (detected by MPI) was greater in subjects with diabetes than in subjects without diabetes, and more abnormalities were found in those with poor glycemic control. 12 Similarly, Ravipati et al noted that higher HbA 1c levels were associated with more severe angiographically determined CAD.¹³…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“… 40 Lynn Fillipon et al discovered that long-term glycemic control in patients with diabetes can weaken CHD and its associated complications. 41 …”
Section: Discussionmentioning
confidence: 99%